2002
DOI: 10.1097/00002030-200203080-00018
|View full text |Cite
|
Sign up to set email alerts
|

‘Barebacking’ in a diverse sample of men who have sex with men

Abstract: New approaches are needed to reduce bareback behavior and the risk of HIV transmission, including innovative health-promoting behavioral and biomedical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
145
0
16

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 13 publications
10
145
0
16
Order By: Relevance
“…Together, these findings suggests that some MSM may be employing strategic positioning (i.e., unprotected insertive rather than receptive anal intercourse) to reduce their perceived risk of HIV/STI acquisition and is consistent with previous work documenting the practice as a harm-reduction strategy among MSM who practice unprotected sex. [3][4][5][6] It has been suggested that, for some gay men, condomless sex may be a manifestation of a need to assert the transgressional aspect of their non-mainstream sexuality. 23 Placing transgression or resistance at the core of understanding barebacker identity-where identifying against norms constitutes a type of power over normative structures-is consistent with the cultural and historical emergence of gay male identity which rose in opposition to mainstream heterosexuality during the gay liberation movement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Together, these findings suggests that some MSM may be employing strategic positioning (i.e., unprotected insertive rather than receptive anal intercourse) to reduce their perceived risk of HIV/STI acquisition and is consistent with previous work documenting the practice as a harm-reduction strategy among MSM who practice unprotected sex. [3][4][5][6] It has been suggested that, for some gay men, condomless sex may be a manifestation of a need to assert the transgressional aspect of their non-mainstream sexuality. 23 Placing transgression or resistance at the core of understanding barebacker identity-where identifying against norms constitutes a type of power over normative structures-is consistent with the cultural and historical emergence of gay male identity which rose in opposition to mainstream heterosexuality during the gay liberation movement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with samples of mixed HIV-infected and uninfected MSM have found high rates of intentional unprotected anal intercourse, ranging from 14% to 46%. [2][3][4][5][6] Previous research has also shown HIVinfected MSM to be significantly more likely than HIV-uninfected MSM to report barebacking behavior. 5,6 In studies exclusively of HIV-infected MSM, the frequency of barebacking has been shown to be as high as 84%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral HIV prevention may be particularly challenging for substance-using MSM due to competing physical and emotional needs [17], as well as direct and indirect effects of methamphetamine use. Prior studies have reported on a successful intensive drug treatment model for methamphetamine users to reduce drug use and related harms [18].…”
mentioning
confidence: 99%